Blood pressure, heart rate and its autonomic modulation in malnourished rats at different ages - Bruna da Rosa Maggi Sant’Helena; Maria do Socorro Brasileiro-Santos; Elis Pereira Falcão; Denia Palmeira Fittipaldi Duarte; Nicodemos Telles de Pontes Filho; Carlos Peres da Costa (Acta Scientiarum. Biological Sciences, 2014)
Malnutrition is responsible for a number of alterations that occur in the organism, including alterations in the cardiovascular system. We hypothesize that long periods of malnutrition occurring after weaning may also be responsible for alterations in the cardiovascular system. Wistar rats were separated into the two following experimental groups: a labina® diet-fed control group (CG) and a malnourished group (MG), fed a multi-deficient diet. Results showed that the mg presented significantly lower body weight (p < 0.001) in rats of all ages, higher heart rate (HR) (p < 0.05) when rats were 3, 4 and 5 months old and lower HR in rats from 6 to 9 months of age, in relation to the CG. Spectral analysis showed a significant increase in the low frequencies (LF) components in the MG compared to the CG from the third month onwards (p < 0.05), showing evidence of sympathetic predominance greater cardiac autonomic balance in the MG versus that of CG indicated that, although aging influences autonomic behavior, it may also be altered by nutrition. Morphologically, an increase in the ventricle weight/body weight ratio was seen in the MG. These results show that the hearts of rats in the MG were not spared from malnutrition age-related detrimental cardiac effects associated with malnutrition